2005
DOI: 10.1111/j.1471-4159.2004.02925.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of death receptor and mitochondrial‐dependent apoptosis by c‐Jun N‐terminal kinase in hippocampal CA1 neurones following global transient ischaemia

Abstract: c-Jun N-terminal kinase (JNK), a member of the mitogenactivated protein kinase family, is activated in response to a number of extracellular stimuli, including inflammatory cytokines, UV irradiation and ischaemia. A large body of evidence supports a role for JNK signalling in stress-induced apoptosis. It has been hypothesized that JNK may contribute to the apoptotic response by regulating the intrinsic cell death pathway involving the mitochondria. Here, we examined the role of the JNK signalling pathway in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 30 publications
3
38
0
1
Order By: Relevance
“…This may be because of early cell death by necrosis during the initial HII; delayed cell death by apoptosis (a relatively late event in this model) might therefore be specifically associated with JNK3 activation. In support of this notion, continuous JNK activation is required for several hours for neuronal apoptosis induced by HII and even the relatively late inhibition of JNK after injury is still protective (Borsello et al, 2003;Carboni et al, 2005). After cerebral HII, the combined activation of excitatory amino-acid receptors and the increased formation of oxygen free radicals and of intracellular Ca 2 + (Takita et al, 2004) are possible triggers for JNK3 activation.…”
Section: Discussionmentioning
confidence: 92%
“…This may be because of early cell death by necrosis during the initial HII; delayed cell death by apoptosis (a relatively late event in this model) might therefore be specifically associated with JNK3 activation. In support of this notion, continuous JNK activation is required for several hours for neuronal apoptosis induced by HII and even the relatively late inhibition of JNK after injury is still protective (Borsello et al, 2003;Carboni et al, 2005). After cerebral HII, the combined activation of excitatory amino-acid receptors and the increased formation of oxygen free radicals and of intracellular Ca 2 + (Takita et al, 2004) are possible triggers for JNK3 activation.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, increased cytochrome c release has been detected in ischemic tissues in animal models (38). In a previous study, we showed that global transient ischemia in the gerbil model induces two waves of apoptosis; however, only the second one is associated with significant cytochrome c release (41). The first wave is associated with caspase-8 activation, whereas activation of caspase-3 is detected in both waves.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Therefore, it was hypothesized that (G2019S) LRRK2 causes degeneration of SNpc dopaminergic neurons in (G2019S) LRRK2 mice by promoting the formation of active caspase-9, caspase-8, and caspase-3. In accordance with this hypothesis, protein level of cleaved active caspase-9, active caspase-8, or active caspase-3 was greatly increased in the SN of 12-month-old (G2019S) LRRK2 mice (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%